Attentional Demands of Walking in Athletes with and without Functional Ankle Instability - Armaghan Mahmoudian; Behnam Akhbari; Mahyar Salavati (Journal of Rehabilitation, 2010)
Objective: By mentioning this fact that the athletes have to be multi-tasking in the field in spite of injury, it seems vital to investigate the attentional demands of walking in these subjects.